Role of rumination and hope on negative life events and suicidal ideation under the background of normalization of pandemic prevention and control: A moderated mediation model - Yao, Yingying; Qiao, Zhihong; Dong, Fangbai; Ni, Jianchao (Frontiers in Public Health, 2023)
Introduction The study aimed to investigate the impact and mechanism of negative life events on college students' suicidal ideation during the COVID-19 pandemic and the buffering effect of hope under the background of normalization of pandemic. Methods A total of 5211 participants took part in this study. Self-reported negative life events, rumination, hope and suicide ideation were measured using a range of questions and scales. Our research demonstrated that the incidence of suicidal ideation among college freshmen in the past week was higher during the COVID-19 pandemic than that before the pandemic. In this study, conditional process model 15 was used to verify the hypothetical model of rumination as a potential mediator and hope as a moderator. Results The hypothesized moderated mediation model was verified significant (β = -0.047, 95% CI = [-0.061, -0.035]), and hope was found to moderate the direct effect of negative life events on suicidal ideation (β = -0.039, t = -2.937, 95% CI = [-0.065, -0.013]) as well as the indirect effect of through the mediator rumination (β = -0.134, t = -10.850, 95% CI = [-0.158, -0.110]). Discussion We found that rumination partially mediated the effect of negative life events on suicidal ideation, and hope buffered the direct and indirect effect of negative life events on suicidal ideation. The implications of the findings for clinical interventions are discussed, including the importance of hope arousal as a protective factor and rumination as a cognitive mechanism for emotion regulation under the background of normalization of pandemic.